2000
DOI: 10.1080/08927010009386299
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical factors favoring release from fouling release coatings

Abstract: For some twenty years the marine coatings industry has been intrigued by polymer surfaces with low adhesion to other materials, especially to the biological glues used by marine organisms. Polymers with fouling release surfaces have been made from sundry materials, and their resistance to marine fouling in both static and dynamic tests has been evaluated in the world's oceans. Although the polymer surface property most frequently correlated with bioadhesion is its critical surface tension (γ(?)), resistance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
263
0
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 422 publications
(276 citation statements)
references
References 21 publications
6
263
0
7
Order By: Relevance
“…Indeed, pull-off tests of epoxy bonded to silicone coatings (often called pseudobarnacle tests) have verified the behavior predicted by Kendall's model (Kohl & Singer, 1999;Brady & Singer, 2000;Singer et al 2000). However, the only two published reports to date using live animals (in contrast to pseudobarnacles) failed to find an inverse relationship between coating thickness and pull-off force Sun et al 2004).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Indeed, pull-off tests of epoxy bonded to silicone coatings (often called pseudobarnacle tests) have verified the behavior predicted by Kendall's model (Kohl & Singer, 1999;Brady & Singer, 2000;Singer et al 2000). However, the only two published reports to date using live animals (in contrast to pseudobarnacles) failed to find an inverse relationship between coating thickness and pull-off force Sun et al 2004).…”
mentioning
confidence: 92%
“…Brady & Singer, 2000; non-toxic coatings allow biofouling to occur and Singer et al 2000;; Chaudhury instead rely on the inability of organisms to adhere et al 2004), frictional slippage (Newby et al 1995; well to surfaces. Weak adhesion by organisms Newby & Chaudhury, 1997), and coating thickness facilitates their removal through factors such as biotic (Kohl & Singer, 1999;Brady & Singer, 2000). disturbance or hydrodynamic forces (e.g.…”
mentioning
confidence: 99%
“…Despite the difficulty with Kendall's model (e.g. K ¼ 1 for incompressible materials), pull-release experiments using rigid studs showed that the pull-off force scales reasonably well with 1= ffiffiffi h p [21,29]. This paradoxical result can be explained by a recent work of Chung & Chaudhury [29], who pointed out that the incompressible constraint in the thin elastic layer will lead to cavitation on the punch-layer interface, which is also observed by Kohl & Singer in an earlier work [22].…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, we treat the geometric case of an acorn-shaped barnacle with a hard calcarious base plate. A common method to test the effectiveness of a fouling-release coating is to determine the force needed to pull a rigid cylindrical flat punch bonded to a thin layer of elastomer [21][22][23]. The rigid flat punch or stud is often referred to as a pseudo-barnacle and the thin elastic layer represents the release coating.…”
Section: Introductionmentioning
confidence: 99%
“…An integrated removal strategy first exposes biofilms to sublethal concentrations of antibiotics or other chemical agents, which can lead to reduced stiffness and enhanced removal, although crosslinkers and multivalent ions can increase stiffness [55,106]. In addition, modifying the topographic, chemical or elastic properties of abiotic surfaces can reduce cell attachment or promote weak bonding that can be more easily removed [13,24,33,35,49].…”
Section: Introductionmentioning
confidence: 99%